2011
DOI: 10.1136/bjo.2010.199562
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mild papilloedema using spectral domain optical coherence tomography

Abstract: PTR thickness measurement increases the sensitivity of detection of mild PO compared with conventional RNFL measurement. This new way of using OCT may be useful for clinicians to detect mild PO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 18 publications
2
45
2
1
Order By: Relevance
“…At present, no single method has prevailed, so further research is required in order to find and optimize a noninvasive method of measuring ICP that is reliable, easy to use, and cost-effective. [62] ▪ No comparison to invasively measured ICP ▪ OCT parameter peripapillary total retinal thickness (PTR) is a sensitive indicator of mild papilledema Ahuja et al [63] ▪ No comparison to invasively measured ICP ▪ Positive correlation between Frisen grading of papilledema and OCT parameter retinal nerve fiber layer (RNFL) thickness with r = 0.80…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…At present, no single method has prevailed, so further research is required in order to find and optimize a noninvasive method of measuring ICP that is reliable, easy to use, and cost-effective. [62] ▪ No comparison to invasively measured ICP ▪ OCT parameter peripapillary total retinal thickness (PTR) is a sensitive indicator of mild papilledema Ahuja et al [63] ▪ No comparison to invasively measured ICP ▪ Positive correlation between Frisen grading of papilledema and OCT parameter retinal nerve fiber layer (RNFL) thickness with r = 0.80…”
Section: Resultsmentioning
confidence: 98%
“…The correlation between OCT and Frisen grading for papilledema has been demonstrated in several studies [62][63][64]. One study found a positive correlation between Frisen grading and RNFL thickness with r = 0.7952 [63].…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 93%
See 1 more Smart Citation
“…9) measures as described are found to have better sensitivity for detecting disc edema when compared with circumpapillary RNFL measures. [31][32][33] …”
Section: Circumpapillary Retinal Nerve Fiber Layer Analysismentioning
confidence: 99%
“…Subsequently, total retinal thickness measured at the ONH is found to be sensitive in detecting subclinical changes. [31][32][33] When disc edema is secondary to elevated ICP, quantitative or qualitative assessment of the retinal pigment epithelium angle can be used to assess changes to treatment. 11,47 Specifically, as ICP decreases, there is downward shift in the optic nerve head when compared with the circumpapillary tissue.…”
Section: Increased Retinal Nerve Fiber Layermentioning
confidence: 99%